A new species of the genus Tropiocolotes Peters, 1880 from western Iran (Squamata: Sauria: Gekkonidae) - Krause, Valentina (Zootaxa, 2013)
The genus Tropiocolotes comprises small, naked toed, ground dwelling and nocturnal desert geckos, ranging from Morocco and Mauritania in northern Africa to south and central Arabia as well as coastal Iran. Herein, we describe a new species of the genus Tropiocolotes from western Iran based on five specimens from Nayband region. This new taxon is described with a statistical approach based on 34 meristic, metric and qualitative morphological characters of more than 300 individuals of related species.